Fashion marketing in the metaverse - Yogesh Dwivedi (Journal of Global Fashion Marketing, 2024)
The metaverse is a shared virtual environment with significant implications for several aspects of businesses. This conceptual paper focuses on how fashion brands can benefit from the metaverse’s vast opportunities. Reviewing the key publications in this field, it identifies the key stakeholders who shape fashion marketing in the metaverse: fashion brands, tech developers, and consumers. Furthermore, the paper outlines the opportunities and challenges of fashion marketing in the metaverse. The study presents a conceptual framework that shows the collaborative relationships between critical stakeholders involved in fashion marketing to take such opportunities and overcome potential challenges. The framework provides a theoretical foundation for research and practice in fashion marketing within the metaverse. The study contributes to the expanding body of research on the intersection of the metaverse and fashion marketing, offering valuable managerial insights for fashion brands and tech developers and a rich agenda for future research.